2022
DOI: 10.1101/2022.02.28.22271467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imported SARS-COV-2 Variants of Concern Drove Spread of Infections Across Kenya During the Second Year of the Pandemic

Abstract: Background. Using classical and genomic epidemiology, we tracked the COVID-19 pandemic in Kenya over 23 months to determine the impact of SARS-CoV-2 variants on its progression. Methods. SARS-CoV-2 surveillance and testing data were obtained from the Kenya Ministry of Health, collected daily from 306 health facilities. COVID-19-associated fatality data were also obtained from these health facilities and communities. Whole SARS-CoV-2 genome sequencing were carried out on 1241 specimens. Results. Over the pande… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…We document multiple introductions of each VOC and subsequent local community transmission in the county. Sequential replacement of the VOCs was observed; from Alpha to Delta, to Omicron over the seven month period, as also observed in other regions within the country and globally 4,5,11 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We document multiple introductions of each VOC and subsequent local community transmission in the county. Sequential replacement of the VOCs was observed; from Alpha to Delta, to Omicron over the seven month period, as also observed in other regions within the country and globally 4,5,11 .…”
Section: Discussionsupporting
confidence: 71%
“…During the first two waves of infection, the dominant lineages were mainly B.1 and B.1.1 3 . However, in early 2021 the VOCs replaced the ancestral strain lineages to drive the three subsequent major waves of infection, observed between March and December 2021 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Until September 2022, Kenya had experienced six major waves of SARS-CoV-2 infections 23 . The current study coincided with national waves three, four, and five, a period during which Alpha (B.1.1.7) , Delta (B.1.617.2) and Omicron (B.1.1.529) variants of concern (VOC) predominated, respectively 24 . We undertook detailed genomic analysis to identify independent SARS-CoV-2 introductions into households during clustered infections, and understand frequency of infection spread within households in coastal Kenya.…”
Section: Introductionmentioning
confidence: 65%
“…The characteristics of this trend matched very well with the national tracking which contained a larger sample size, giving external validity to the data set. Genomic epidemiology studies in the country revealed that the first two waves were predominantly caused by the original SARS-CoV-2 strain, while the third, fourth, and fifth were caused by the Alpha, Delta , and Omicron variants, respectively ( 20 ). The trend of the percentage of patients in ICU generally followed the positivity rate with less accentuated peaks.…”
Section: Resultsmentioning
confidence: 99%